A case report of apical aneurysms and myocardial perfusion deficit with myocardial necrosis due to hypertrophic cardiomyopathy. Issue 21 (May 2018) - Gao, Xiangyu; Yang, Jigang; Zhang, Xiaojie; Wang, Ping; Li, Hongwei
Abstract: Rationale: Hypertrophic cardiomyopathy (HCM) is a disease that is characterized by inappropriate left ventricular and/or right ventricular hypertrophy and hypercontractility that is often asymmetrical and associated with microscopic evidence of myocardial fiber disarray. The aim of this study was to present a previously under-recognized subset of HCM patients with left ventricular (LV) apical aneurysms. Patients concerns: A 33-year-old man who presented with chest discomfort for 10 days. He had an emerging apical aneurysm in the LV without midventricular obstruction. He had been diagnosed with apical HCM via abnormal electrocardiograms (ECG) and single-photon emission computed tomography (SPECT) for 10 years. This time, a new significant change in ECG and SPECT was identified. Late gadolinium enhancement (LGE) was observed by cardiac magnetic resonance imaging (MRI), and SPECT showed myocardial fibrosis or necrosis involving the apical aneurysm and proximal portion of the heart, which was confirmed by left ventriculography. Diagnoses: We present a relatively rare case of HCM patients with apical aneurysms, accompaning by myocardial necrosis markers increased due to ventricular muscle stress increases, rather than obstructive coronary artery disease. Interventions: The patient was prescribed aspirin, metoprolol tartrate, perindopril, and atorvastatin and was strongly advised to quit cigarettes and reduce weight. Outcomes: Follow-up at half a year turned out well. Lessons: LGE with a notable progression by ECG and SPECT along with an increase in myocardial necrosis markers in HCM patients with apical aneurysms, as was noted in the present case, is a relatively rare occurrence. Our present case may provide unique insights into the adverse remodelling process and the formation of apical aneurysms in HCM patients.